Multishot Diffusion‐Weighted MRI of the Breast With Multiplexed Sensitivity Encoding (MUSE) and Shot Locally Low‐Rank (Shot‐LLR) Reconstructions. Issue 3 (16th October 2020) - Hu, Yuxin; Ikeda, Debra M.; Pittman, Sarah M.; Samarawickrama, Dilan; Guidon, Arnaud; Rosenberg, Jarrett; Chen, Shu‐tian; Okamoto, Satoko; Daniel, Bruce L.; Hargreaves, Brian A.; Moran, Catherine J.
Abstract : Background: Diffusion‐weighted imaging (DWI) has shown promise to screen for breast cancer without a contrast injection, but image distortion and low spatial resolution limit standard single‐shot DWI. Multishot DWI methods address these limitations but introduce shot‐to‐shot phase variations requiring correction during reconstruction. Purpose: To investigate the performance of two multishot DWI reconstruction methods, multiplexed sensitivity encoding (MUSE) and shot locally low‐rank (shot‐LLR), compared to single‐shot DWI in the breast. Study Type: Prospective. Population: A total of 45 women who consented to have multishot DWI added to a clinically indicated breast MRI. Field Strength/Sequences: Single‐shot DWI reconstructed by parallel imaging, multishot DWI with four or eight shots reconstructed by MUSE and shot‐LLR, 3D T2 ‐weighted imaging, and contrast‐enhanced MRI at 3T. Assessment: Three blinded observers scored images for 1) general image quality (perceived signal‐to‐noise ratio [SNR], ghosting, distortion), 2) lesion features (discernment and morphology), and 3) perceived resolution. Apparent diffusion coefficient (ADC) of the lesion was also measured and compared between methods. Statistical Tests: Image quality features and perceived resolution were assessed with a mixed‐effects logistic regression. Agreement among observers was estimated with a Krippendorf's alpha using linear weighting. Lesion feature ratings were visualized using histograms, and correlation coefficients of lesion ADC between different methods were calculated. Results: MUSE and shot‐LLR images were rated to have significantly better perceived resolution ( P < 0.001), higher SNR ( P < 0.005), and a lower level of distortion ( P < 0.05) with respect to single‐shot DWI. Shot‐LLR showed reduced ghosting artifacts with respect to both MUSE ( P < 0.001) and single‐shot DWI ( P < 0.001). Eight‐shot DWI had improved perceived SNR and perceived resolution with respect to four‐shot DWI ( P < 0.005). Data Conclusion: Multishot DWI enables increased resolution and improved image quality with respect to single‐shot DWI in the breast. Shot‐LLR reconstructs multishot DWI with minimal ghosting artifacts. The improvement of multishot DWI in image quality increases with an increased number of shots. Level of Evidence: 2 Technical Efficacy Stage: 2